Screening for hypertrophic cardiomyopathy. Issue 10 (October 2021) - Pydah, Sunayana C.; Mauck, Kimberlee; Shultis, Chelsea; Rolfs, Jenna; Schmidt, Eric; Nicholas, Joyce
Abstract : ABSTRACT: Hypertrophic cardiomyopathy (HCM) is the most common inherited cardiomyopathy and causes changes in the cardiac muscle affecting ventricular, valvular, and cellular functions. Because HCM is an inherited disorder, all age groups are affected; however, it commonly presents in adolescents, especially athletes. Many patients are asymptomatic and undiagnosed, putting them at risk for sudden cardiac death. This article describes screening and management of patients with HCM.